THE RISK PHENOMENON OF INVESTING IN CAPITAL MARKET (INDIVIDUAL BROKER PERCEPTION) - Ang Swat Lin Lindawati; Tiffany Roselin (Journal of Economics, Business, and Accountancy Ventura, 2013)
This exploratory study is concerned with phenomenon of the risk of investing in capital market,which is often distressing and being perceived negatively by public/investors. Intentionally,it’s establishing the main reasons for the public lack of interest toward capital marketinvestment products. The understanding of professional perception in capital market such asbroker relies on the phenomenon of risk of investing in capital market had been proposed ofthis study. Therefore, phenomenology research approach is chosen to reveal participant perceptionbased on participant’s experiences through in depth interview technique. The resultof this exploratory suggests that trust may become one of key element to change public’s perception,which very often already negative toward capital market. Investors need securityassurance toward the investment fund; the broker must be able to assure the trust that hasbeen given by the investor through the verification of the broker’s capabilities and knowledge.